DEVELOPMENT OF PHYSICAL QUALITIES IN YOUNG VOLLEYBALL PLAYERS THROUGH ACTIVE GAMES (Eureka Journal of Education & Learning Technologies, 2026)
The article provides a scientific and pedagogical analysis of the role and effectiveness of active games in developing physical qualities in young volleyball players. The study was conducted as a pedagogical experiment involving students of a secondary specialised educational institution, who were divided into experimental and control groups. In the experimental group, training sessions were organised on the basis of specially selected active games, while the control group followed conventional exercises. The results of the four-week experiment showed that game-based training developed speed, strength, agility and endurance significantly more effectively than the conventional approach. The game-based approach was also found to increase athletes’ interest in training, their activity and their teamwork. The findings are of significant scientific and practical importance for improving the preparation of young volleyball players.
Keywords: active games, volleyball, young athletes, physical qualities, speed, agility, endurance, strength, coordination, training process, sports pedagogy, pedagogical experiment.